ENERGY EFFICIENCY OF ENERGY SUPPLY SYSTEMS, BASED ON COMBINED COGENERATION HEAT PUMP INSTALLATIONS АND PEAK SOURCES OF HEAT - Ostapenko, Olga (Scientific Works of Vinnytsia National Technical University, 2016)
The approach to evaluation of energy efficiency of energy supply systems (ESS), based on combined cogeneration heat pump installations (CHPI) and peak sources of heat (PSH), taking into consideration complex impact of variable operation modes, sources of drive energy for steam compressor heat pump installations (HPI) of various power levels, with the account of energy losses in the process of generation, supply and conversion of electric energy, is suggested.